2022
DOI: 10.3390/ma15186482
|View full text |Cite
|
Sign up to set email alerts
|

Alkalizing Properties of Six Calcium-Silicate Endodontic Biomaterials

Abstract: Introduction: Calcium silicate-based cements (CSC), are self-setting hydraulic biomaterials widely used for reparative procedures in dentistry and endodontics. These materials possess physical properties, such as ion release, porosity, solubility, and radiopacity. Their biological properties are connected to their alkalizing activity and calcium release capacity. Materials and Methods: Six calcium silicate-based materials were selected for this study: TheraCal LC (Bisco Inc., Schaumburg, IL, USA), MTA Plus (Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The undiluted extracts were prepared from the set materials using a basal control medium as the extraction solution, which was further diluted for the exposure experiments (1%, 10%, and 20% extracts). The undiluted extracts showed a pH~9.5, thus exhibiting the alkalinizing effect normally described for these formulations [ 53 , 54 ]. However, due to the buffering effect of the medium, the pH of the diluted extracts was kept at ~7.4, similar to that of the extracellular fluid.…”
Section: Discussionmentioning
confidence: 80%
“…The undiluted extracts were prepared from the set materials using a basal control medium as the extraction solution, which was further diluted for the exposure experiments (1%, 10%, and 20% extracts). The undiluted extracts showed a pH~9.5, thus exhibiting the alkalinizing effect normally described for these formulations [ 53 , 54 ]. However, due to the buffering effect of the medium, the pH of the diluted extracts was kept at ~7.4, similar to that of the extracellular fluid.…”
Section: Discussionmentioning
confidence: 80%
“…In the current study, calcium exhibited statistically significant changes between the initial and final measurements for the following materials: ProRoot MTA (increase), MTA Angelus (decrease), Biodentine (decrease), and TheraCal (increase). CSM materials also provide significantly more alkaline pH (9.5-13) than RBM materials; this may indicate an antibacterial capability and enhanced mineralisation [41,54,55]. The highest levels of phosphorous were detected in TheraCal LC (16.39 after 24 h and 17.00 after 28 days) followed by MTA Angelus (0.14 after 24 h and 14.81 after 28 days), ProRoot MTA (0.14 after 24 h and 5.96 after 28 days), Activa BioActive Base/Liner (1.61 after 24 h and 0.70 after 28 days), Predicta Bulk, Biodentine, and Activa Presto.…”
Section: Discussionmentioning
confidence: 99%
“…Distilled water (DW) served as the reference group for comparison due to its well-established efficacy as a vehicle for tricalcium silicate cement and its widespread use by manufacturers [36]. The pH value of Biodentine discs (5 mm × 10 mm) in DW has been reported to range from 11.2 after 1 day to 11.3 after 7 days [36], and other study disc size (4 mm × 5 mm) showed 9.65 to 11.5 after 14 days [38]. A Biodentine powder (5 mg/mL) showed a mean pH value of 11.32 after 7 days [39].…”
Section: Discussionmentioning
confidence: 99%